الوظيفة النقدية للتربية والعملية التعليمية وفق المدخل السوسيولوجيالتربوي لدوركهايم - علي شريف, حورية; دحماني, سمراء (دفـاتر المـــــــــــخبـر; No 16 (2016): مجلة دفاتر, 2018)
الملخص: يعتبر دوركهايم من أبرز رواد الاتجاه الوظيفي،وأكثرهم تأثيرا في تطور النظرية السوسيولوجية. تتميز أعماله بتنوع اهتماماتها، وتأسيسها للأسس العلمية والمنهجية لعلم الاجتماع، وقد وضع تصوره وبسط تحليلاته حول علم اجتماع التربية من خلال كتابه  التربية وعلم الاجتماع، حيث نظر إلى التربيةبأنها شيء اجتماعي بإمكانها أن يغير المجتمع ككل. واعتبر المدرسة الوسط الاجتماعي الذي يحدد الأفكار والمثل والقيم، والتي هي من أهم مقومات الحياة الجمعية. نهدفمنخلالهذاالعملعرضأهمأفكارهوالقضاياوالافتراضاتالتيطرحهافيمجالسوسيولوجياالتربية،للتعرفعلىمشروعهالسوسيولوجيالتربوي. Abstract : Durkheim is one of the leading career leaders, and most influential in the evolution of sociological theory. His work is characterized by a variety of interests and the establishment of the scientific and methodological foundations of sociology. He developed his conception and extended his analysis on the sociology of education through his book Education and Sociology. He considered education as a social thing that could change society as a whole. And values, which are among the most important elements of life. The school is considered as the social environment that defines ideas, ideals and values, which are among the most important elements of social life. Through this work, we aim to present his most important ideas, issues and assumptions in the field of sociology of education, to identify his educational sociological project.